The Evolution of Correctional Program Assessment in the Age of Evidence-Based Practices. Issue 2 (3rd April 2018) - Duriez, Stephanie A.; Sullivan, Carrie; Latessa, Edward J.; Lovins, Lori Brusman
ABSTRACT: As evidence-based practices becomes an increasingly popular term, it is crucial that correctional programs are assessed to ensure that research is being translated and implemented with fidelity. Too often the corrections field is quick to treat different interventions as a panacea, without truly understanding how the program does or does not meet the literature on effective practices. Data is provided based on decades of assessment using the Correctional Program Assessment Inventory and the Evidence-Based Correctional Program Checklist. Findings suggest program adherence to effective practices has shown some improvement, but still has a way to go, particularly in the area of treatment characteristics and quality assurance.